Plate 7: Lixiviating tubs; filtration fountain; chemical lamp furnace; distillatory apparatus; mortars - Accum, Friedrich Christian (An Explanatory Dictionary of the Apparatus and Instruments Employed in the Various Operations of Philosophical and Experimental Chemistry, 1824)
Depicts lixiviating tubs in figure 1, a filtration fountain in figure 5, chemical lamp furnace in figure 6, compound distillatory apparatus in figure 14, as well as an alembic, hydrostatic balance, hydrometer, and iron and steel mortars.
Keywords: Chemistry; Chemical apparatus